2008
DOI: 10.1007/s12230-008-9011-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Potato (Solanum tuberosum L.) to Green Manure Cover Crops and Nitrogen Fertilization Rates

Abstract: This study compared the effects of common vetch (Vicia sativa L.), faba bean (Vicia faba L.), and winter wheat (Triticum aestivum L.; control) cover crop green manures in combination with four rates of nitrogen (N) on tuber yield and quality of three potato varieties (Marfona, Hermes and Agria) during 2-years (2004)(2005). Results over years were combined for final analysis. Above-ground dry matter for common vetch and faba bean green manure crops were 2,300 and 2,587 kg ha −1 , respectively. Mean root dry mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The hairy vetch both in pure stand and in mixture with oat and subclover produced an abundant biomass as observed in previous research (Isik et al 2009;Sincik et al 2008;Brennan and Smith 2005). According to Wagger (1989), the quantity of legume CC biomass had a great impact on the total N accumulation.…”
Section: Discussionsupporting
confidence: 63%
“…The hairy vetch both in pure stand and in mixture with oat and subclover produced an abundant biomass as observed in previous research (Isik et al 2009;Sincik et al 2008;Brennan and Smith 2005). According to Wagger (1989), the quantity of legume CC biomass had a great impact on the total N accumulation.…”
Section: Discussionsupporting
confidence: 63%
“…As stated in some previous studies, the economic optimum nitrogen rate (EONR) was closely related to the fertilizer N price/crop value ratio (Belanger et al, 2000;Andraski, Bundy, 2005;Sincik et al, 2008), and the EONR was reported to be 100-110 kg ha -1 N to achieve good sunflower production (Ayup et al, 1998;Malik et al, 2004;Peker, Ozer, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…Cover crops fit well into potato production systems, where they have been shown to improve soil properties, suppress soilborne diseases, and increase tuber yields (Sincik et al, 2008;Campiglia et al, 2009;Griffin et al, 2009). However, little is known about their effects on insect pests.…”
Section: Cover Cropsmentioning
confidence: 99%